Adolescent Delinquency And Drug Abuse: An Analysis Of Psychological And School Environmental Factors At Gema Karya Bahana Vocational High School, Bekasi - Rahayu Khairiah; Nurmanita Dewi (Universitas Pahlawan Tuanku Tambusai, 2026)
Juvenile delinquency and drug abuse are problems that still frequently occur in school environments and can have a negative impact on adolescent development. Various factors are thought to play a role in the emergence of such behavior, particularly environmental and psychological factors. This study aims to identify and analyze the relationship between environmental and psychological factors and juvenile delinquency and drug abuse in the school environment of Vocational High School Gema Karya Bahana Bekasi. This study used a quantitative approach with a correlational design. The study population consisted of 226 students, with a sample of 144 respondents determined using the Slovin formula. Data collection was conducted using a questionnaire with a Likert scale that measured environmental factors, psychological factors, juvenile delinquency, and drug abuse. Data analysis included univariate analysis to describe the characteristics of each variable and bivariate analysis to determine the relationship between variables. Bivariate analysis was performed using Spearman's rho nonparametric correlation test with a significance level of α = 0.05. The results of the study show a positive and significant relationship between environmental factors and juvenile delinquency (rₛ = 0.272; p = 0.001) and between environmental factors and drug abuse (rₛ = 0.379; p = 0.000). Conversely, psychological factors did not show a significant relationship with either juvenile delinquency or drug abuse. The conclusion of this study shows that environmental factors play a more dominant role in influencing juvenile delinquency and drug abuse in the school environment than psychological factors.